Dietary Habits of Type 2 Diabetes Patients: Variety and Frequency of Food Intake - Senadheera Pathirannehelage Anuruddhika Subhashinie Senadheera; Sagarika Ekanayake; Chandanie Wanigatunge (Journal of Nutrition and Metabolism, 2016)
The objective of the present study was to observe the dietary patterns and food frequencies of type 2 diabetes patients attending the clinics of the Family Practice Center of the University of Sri Jayewardenepura, located in a highly urbanized area in Sri Lanka. An interviewer administered questionnaire based cross-sectional study was conducted among randomly selected 100 type 2 diabetes patients [age 35–70 years; mean age 55±9 (males = 44; females = 56)]. The data were analyzed by SPSS version 18.0 software. Vegetables, fatty foods, and poultry consumption were in accordance with the national guidelines. A significant percentage (45.5%) consumed rice mixed meals for all three meals and only 67% consumed fruits at least once a day. Majority (71%) consumed full-cream milk and sugar intake (77%) was in accordance with the guidelines. Noncaloric sweetener usage was nonexistent. Daily green leafy vegetable intake and the quantity consumed were inadequate to obtain beneficial effects. From the study population, 44% [females 50%; males 36%] of the patients were either overweight or obese. However, only 60% of those patients accepted that they were either overweight or obese. Only 14% exercised daily while 69% never exercised. Study revealed the importance of educating patients with type 2 diabetes on dietary changes and more importantly the involvement in regular physical exercises.